Role of Traditional Ecological Knowledge in Natural Resource Management among Monpas of North-western Arunachal Pradesh - Saha, Somidh; Bisht, N. S. (Indian Forester, 2007)
This paper describes the role of traditional ecological knowledge and wisdom of the Monpa tribe in the management of natural resources like water, soil and forest in the high altitudes of the Eastern Himalayas. The traditional water resource management practices are highly diversified and have multipurpose uses. People have developed irrigation system using gravitational force that check surface runoff and maintain the water table throughout the year. They have unique technique for pre-detection of the flash flood using water force. The traditional highland farming system is highly productive, sustainable and environment friendly. The wet paddy cultivation in high altitude valley and intercropping system in terrace cultivation has been described in detail. Both these systems ameliorate soil fertility and have no negative impact on environment. The forests are owned and managed by the community. People follow customary laws and traditions regarding collection of forest products. They follow traditional silvicultural practices for management of their forestland. They have strong religious belief on conservation of plants and animals. The sacred groves concept plays a significant role in this aspect. All these systems have been discussed in detail in present paper.